Perceptual Information Integration: Hypothetical Role of Astrocytes - Pereira, Alfredo [UNESP] (Springer, 2012)
In perceptual processes, signals carrying information about a stimulus are transmitted through multiple processing lines to populations of receptive neurons and thalamocortical circuits, leading to the formation of a spatial ensemble of local field potentials. This paper addresses the problem of how the brain integrates patterns embodied in local fields to (re) construct the stimulus in a conscious episode. Four examples of human perception are given to illustrate the requirements of the integrative process. Considering the strategic position of astrocytes, mediating somatic signals carried by blood flow and information carried by the neuronal network, as well as their intrinsic information processing capabilities, these cells seem ideally placed to integrate spatially distributed information. The amplitude-modulated calcium waveform in astrocytes is a multiscale phenomenon, simultaneously operating on temporal scales of milliseconds and seconds, as well as in micro and macro spatial scales. Oscillatory synchrony, constructive wave interference and communication by means of ionic antennae are proposed to constitute a neuro-astroglial self-organizing mechanism capable of perceptual integration and adding a feeling-like quality to information content. A proposal for constructing an artificial astrocyte is described, which would be capable of testing the hypothesis of astrocytic information integration made earlier.
Keywords: Information integration; Perception; Local field potentials; Astroglial network; Calcium wave